2013
DOI: 10.1177/0954411913478703
|View full text |Cite
|
Sign up to set email alerts
|

Bone remodelling around uncemented metallic and ceramic acetabular components

Abstract: Stress shielding-induced bone resorption around cementless acetabular components has been indicated as a potential failure mechanism that may threaten long-term fixation. Using a bone remodelling algorithm in combination with threedimensional finite element models of intact and implanted pelvises and musculoskeletal loading during normal walking, the objectives of the study were to investigate the deviations in load transfer due to implantation and bone adaptation around cementless metallic and ceramic acetabu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 48 publications
(103 reference statements)
4
70
0
Order By: Relevance
“…Three-dimensional FE models of the intact and implanted pelvises were generated from data from computed tomography (CT) scans of a 62-year-old female patient, similarly to an earlier study (Ghosh, Mukherjee, and Gupta 2013;Ghosh et al 2013b). The generation procedure of the FE model was verified and experimentally validated (Ghosh et al 2012(Ghosh et al , 2013a.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three-dimensional FE models of the intact and implanted pelvises were generated from data from computed tomography (CT) scans of a 62-year-old female patient, similarly to an earlier study (Ghosh, Mukherjee, and Gupta 2013;Ghosh et al 2013b). The generation procedure of the FE model was verified and experimentally validated (Ghosh et al 2012(Ghosh et al , 2013a.…”
Section: Methodsmentioning
confidence: 99%
“…An augmented Lagrange contact algorithm was used for the contact simulation between the femoral head and the acetabular component. The effects of variable implant-bone interface conditions on bone remodelling around uncemented metallic and ceramic acetabular components were investigated by Ghosh, Mukherjee, and Gupta (2013), who observed that the decrease in bone density was maximum for the fully bonded implant-bone interface condition. Accordingly, the fully bonded interface condition was assumed between the bone and implant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A mechanostat principle was applied, based upon the strain history stimulus required to produce a bone volume change (Carter 1984), and implemented using Euler forward integration to calculate iterative changes in the thickness of cortex elements (external remodelling), or the heterogeneous density-and hence the Young's modulus-of trabecular elements (internal remodelling). This method has been applied to femoral implants in THR (Kerner et al 1999;Turner et al 2005), RHR (Gupta et al 2006;Pal et al 2009;Rothstock et al 2011;Dickinson et al 2012;Perez et al 2014), to acetabular cups (Ghosh et al 2013), and in other joints (van Lenthe et al 1997). Advanced approaches have combined strain adaptive bone remodelling with other associated mechanobiological processes, including cementless implant ingrowth (Tarala et al 2011) and periprosthetic defect healing (Dickinson et al 2012).…”
Section: Introductionmentioning
confidence: 99%